Battery positive electrode slurry, positive electrode plate, preparation method of positive electrode plate and battery

By adding a specific proportion of surfactant to the positive electrode slurry of the battery, the problem that the edge thickness of the battery sheet active coating cannot be effectively eliminated is solved, and the uniformity of the thickness of the electrode sheet active coating and the improvement of the battery performance is achieved.

CN119695069AInactive Publication Date: 2025-03-25EVE ENERGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411864220.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the edge thickness of the battery pole sheet active coating cannot be effectively eliminated, resulting in a decay of battery capacity and a shortened life.

Method used

By adding a specific proportion of anionic and nonionic surfactants to the positive electrode slurry of the battery, the viscosity, leveling and thixotropy of the slurry are adjusted, and the dispersion and rheology during the coating process are improved, thereby controlling the edge thickness of the active coating of the electrode sheet.

Benefits of technology

The uniformity of the thickness of the electrode sheet active coating is achieved, the edge thinning effect is improved, the consistency and stability of the battery are improved, and the operation is simple and controllable, and the cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695069A_ABST
    Figure CN119695069A_ABST
Patent Text Reader

Abstract

The invention discloses battery positive electrode slurry, a positive electrode plate, a preparation method of the positive electrode plate and a battery. The positive electrode slurry comprises a positive electrode active material, a conductive agent, a binder, a solvent and a surfactant; the addition amount of the surfactant is 0.01-2wt% of the total amount of the positive electrode slurry; the surfactant is formed by compounding an anionic surfactant and a nonionic surfactant in a weight ratio of (5-15): (85-95). By adding the specific compound surfactant into the slurry, the viscosity, leveling property and thixotropy of the slurry in the pole piece coating process are improved, and the surface energy of the slurry is adjusted, so that the slurry has stable dispersity and a good leveling effect when coating the pole piece, the effect of controlling the edge thickness of a coating is achieved, the thickness uniformity of the pole piece can be improved, and edge thinning can be improved; the method is low in cost, simple to operate and easy to control, does not need to carry out additional processing on the edge, avoids the influence of edge residues, and improves the consistency and stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a battery positive electrode slurry, a positive electrode sheet, a preparation method thereof, and a battery. Background Art

[0002] During the charge and discharge process of lithium batteries, the active materials at the edge of the battery will be subjected to greater stress, resulting in battery capacity attenuation and shortened life. Therefore, the edge of the battery needs to be thinned to reduce the impact of the marginal effect on battery performance. At present, the most commonly used edge thinning method is mechanical thinning, which is to reduce the thickness of the pole piece by cutting, grinding or compression during coating. This method is simple to operate, but it is easy to have edge residues, reduce the consistency of the pole piece, and affect the quality of the battery. Another method is chemical thinning, which mainly corrodes the material at the edge of the battery coating by chemical spraying or immersion to achieve the purpose of thinning. This method is more precise and can achieve a more delicate thinning effect, but the concentration of the thinning agent and the processing time must be strictly controlled during the process, otherwise it will cause irreversible corrosion and damage to the battery.

[0003] Therefore, it is very necessary to find a thinning method that is consistent, gentle, flexible, simple to operate and easy to control. Summary of the invention

[0004] The main purpose of the present application is to provide a battery positive electrode slurry, a positive electrode plate and a preparation method thereof and a battery, so as to solve the problem that the edge thickness of the active coating of the battery plate cannot be effectively eliminated in the prior art.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a battery positive electrode slurry is provided: the components of the battery positive electrode slurry include positive electrode active material, conductive agent, binder, solvent and surfactant; wherein the added amount of surfactant is 0.01-2wt% of the total amount of the battery positive electrode slurry; the surfactant is compounded by anionic surfactant and nonionic surfactant in a weight ratio of (5-15): (85-95).

[0006] Furthermore, the added amount of the surfactant is 0.05-1.5wt% of the total amount of the electrode slurry; further 0.05-1wt%; further 0.08-0.5wt%; further 0.08-0.2wt%.

[0007] Furthermore, the weight ratio of the anionic surfactant to the nonionic surfactant is (5-10):(90-95).

[0008] Furthermore, the anionic surfactant is selected from one or more of ammonium dodecyl alcohol polyoxyethylene ether sulfate, disodium dodecyl alcohol polyoxyethylene ether sulfosuccinate, sodium dodecylbenzene sulfonate, ammonium dodecyl polyacrylate and sodium dioctyl succinate sulfonate.

[0009] Furthermore, the nonionic surfactant is selected from at least one of polyoxyethylene cetyl ether, polyoxypropylene cetyl ether, polyoxyethylene polyoxypropylene cetyl ether, nonylphenol polyoxyethylene ether and ethylhexanol polyoxypropylene polyoxyethylene ether.

[0010] Furthermore, the surfactant consists of disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether.

[0011] Furthermore, the weight ratio of the positive electrode active material, the conductive agent, the binder, the solvent, and the surfactant is (90-95): (1.5-5): (1-4): (0.01-2).

[0012] Furthermore, the viscosity of the battery positive electrode slurry is 4000-5000 mPa·S.

[0013] Furthermore, the solid content of the battery positive electrode slurry is 60% to 70%.

[0014] Furthermore, the positive electrode active material is selected from nickel-cobalt-manganese ternary material; further, the nickel content is ≥50wt%.

[0015] Furthermore, the conductive agent is selected from at least one of conductive graphite, conductive carbon black and carbon nanotubes; further, conductive carbon black.

[0016] Furthermore, the binder is selected from polyvinylidene fluoride.

[0017] Furthermore, the solvent is selected from N-methylpyrrolidone.

[0018] According to the second aspect of the present application, a method for preparing the above-mentioned battery positive electrode slurry is provided, comprising the following steps: mixing raw materials of positive electrode active material, conductive agent, binder, solvent and surfactant according to the ratio of each raw material, stirring to obtain battery positive electrode slurry.

[0019] Furthermore, the preparation method specifically comprises the following steps:

[0020] Step S1: mixing a binder and a solvent to form a glue solution; mixing a conductive agent and a solvent to form a conductive liquid; mixing a surfactant and a solvent to form a surfactant solution;

[0021] Step S2: adding the positive electrode active material to the glue solution and the conductive liquid, adding a solvent to adjust the viscosity for the first time, adding a surfactant solution, and adding a solvent to adjust the viscosity for the second time until the viscosity of the slurry reaches a preset viscosity.

[0022] Furthermore, the mass concentration of the glue solution is 8% to 20%.

[0023] Furthermore, the mass concentration of the conductive liquid is 10% to 12%.

[0024] Furthermore, the mass concentration of the surfactant solution is 0.8% to 1.5%.

[0025] Furthermore, the preset viscosity is 4000-5000 mPa·S.

[0026] According to the third aspect of the present application, a battery positive electrode plate is provided, comprising a positive electrode collector and a positive electrode active coating attached to the surface of the positive electrode collector; the slurry for preparing the positive electrode active coating is the above-mentioned battery positive electrode slurry.

[0027] According to a fourth aspect of the present application, a battery is provided, comprising a positive electrode plate, which is the positive electrode plate of the above-mentioned battery.

[0028] By applying the technical solution of the present application, a battery positive electrode slurry is provided. By adding a specific surfactant to the slurry and the synergistic effect with other components in the slurry, the viscosity, leveling and thixotropy of the slurry in the process of coating the pole piece are improved, and the surface energy of the slurry is adjusted so that the slurry has stable dispersion and good leveling effect when coating the pole piece, thereby playing a role in controlling the thickness of the edge of the active coating of the pole piece, and can achieve the purpose of improving the uniformity of the thickness of the active coating of the pole piece and improving edge thinning. This method is low in cost, simple and easy to control, and does not require additional treatment of the edge of the active coating, thereby avoiding the influence of edge residues and improving the consistency and stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0030] Figure 1 A side structural schematic diagram showing the thickness of the active coating in different areas of the positive electrode plate in an embodiment of the present application is shown.

[0031] Reference numerals:

[0032] 1. Current collector; 2. Coating thickness in the thinned area on one side; 3. Coating thickness in the normal area on one side. DETAILED DESCRIPTION

[0033] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0034] In the prior art, the commonly used treatment methods for the problem of thick edges of battery pole pieces include mechanical thinning, which is to reduce the thickness of the pole piece by cutting, grinding or compression during coating. This method is prone to edge residue, which reduces the consistency of the pole piece and affects the quality of the battery; or chemical thinning is used, which mainly corrodes the material at the edge of the battery coating by chemical spraying or immersion. In this method, the concentration of the thinning agent and the treatment time must be strictly controlled, otherwise it will cause irreversible corrosion and damage to the battery. In order to better improve the problem of thick edges of electrodes without damaging the electrodes, the present application adds a specific proportion of special surfactants to the positive electrode coating slurry, and by adjusting the slurry to have a suitable surface energy, the problem of thick edges of electrodes can be better improved.

[0035] According to one aspect of the present application, a battery positive electrode slurry is provided: the components of the battery positive electrode slurry include positive electrode active materials, conductive agents, binders, solvents and surfactants; wherein the added amount of the surfactant is 0.01 to 2 wt% of the total amount of the battery positive electrode slurry; the surfactant is compounded by anionic surfactants and nonionic surfactants in a weight ratio of (5 to 15): (85 to 95).

[0036] The addition ratio of the surfactant of the present application in the electrode slurry can be adjusted according to actual conditions, for example, any value among 0.01, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.23, 0.25, 0.28, 0.3, 0.35, 0.4, 0.45, 0.50, 0.55, 0.6, 0.65, 0.70, 0.75, 0.80, 0.85, 0.9, 0.95, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0 or any range value between two of them.

[0037] In the present application, the weight proportion of anionic surfactant added is controlled at 5-15, for example, any value among 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or a range between any two of them; the weight proportion of nonionic surfactant is controlled at 85-95, for example, any value among 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, or a range between any two of them.

[0038] The anionic surfactant selected in the present application contains a certain number of polar groups in its molecular chain, which can adsorb solid particles suspended in the slurry to bridge the particles or stabilize the particles through charge neutralization, thereby making the slurry have good dispersibility and rheology, reducing the surface tension of the slurry and improving the edge thickness of the coating during the coating process.

[0039] The non-ionic surfactant selected in the present application is in a non-ionic state in aqueous solution, has high stability, and has good solubility in both water and organic solvents. It can be used in water / oil slurries to promote the uniform dispersion of active substances in different phases, so that the dispersed system has better rheological properties, thereby improving the consistency of thinning the edge of the active coating of the electrode.

[0040] In the positive electrode active slurry of the present application, a good dispersed slurry is formed mainly between a non-ionic surfactant and positive electrode active materials such as nickel-cobalt-manganese ternary materials, a conductive agent, a binder, and a solvent. The non-ionic surfactant can promote the dispersibility of the positive electrode active material in the solvent, thereby making the slurry have good rheological properties; and by adding an auxiliary anionic surfactant, bridging between particles or stabilizing particles by charge neutralization, the dispersibility, rheology and uniformity of the slurry can be further improved, and the surface tension of the slurry can be reduced, so as to improve the edge thickness problem of the coated positive electrode sheet.

[0041] The present application compounds anionic surfactants and nonionic surfactants according to the above-mentioned specific proportions and adds them to the slurry, utilizing their hydrophilic and lipophilic properties to construct a stable connection network in the slurry particles, thereby improving the dispersion and uniformity of the particles in the slurry; and adding a specific proportion of compounded surfactants enables it to have good matching properties with other components in the slurry, synergistically improves the viscosity, leveling and thixotropy of the slurry during the coating of the pole piece, adjusts the surface energy of the slurry, and enables the slurry to have stable dispersion and good leveling effect when coating the pole piece, thereby playing a role in controlling the thickness of the active coating edge, and can achieve the purpose of improving the uniformity of the thickness of the pole piece active coating and improving edge thinning; this method is low-cost, simple and easy to operate, and does not require additional treatment of the active coating edge, thus avoiding the influence of edge residues and improving the consistency and stability of the battery.

[0042] In some embodiments, the amount of surfactant added is 0.01-2wt% of the total amount of the electrode slurry; for example, 0.05-1.5wt%; further 0.05-1wt%; further for example, 0.08-0.5wt%; further for example, 0.08-0.2wt%. The present application found during the trial that when the surfactant ratio is less than 0.01%, it cannot achieve a good effect of reducing the surface tension for edge thinning; when the surfactant ratio is greater than 2%, the slurry viscosity is too low and the surface density is unstable during the coating process, so the ratio is controlled at 0.01-2wt%.

[0043] The present application controls the amount of surfactant added within the above range, which can have better matching with other components in the slurry such as conductive agent, binder, and solvent. The appropriate distribution ratio of each group can play a greater synergistic role with each other, so that the slurry has suitable viscosity, leveling and thixotropy during the coating of the pole piece, and the slurry can be adjusted to have a suitable surface energy, so that the slurry has stable dispersibility and good leveling effect when coating the pole piece, and can better control the thickness of the active coating edge of the pole piece, control the uniformity of the coating thickness, and improve the edge thinning effect. When the above-mentioned composite surfactant selected in the present application is added excessively to the slurry, it will excessively reduce the viscosity of the slurry, which is not conducive to the leveling of the slurry, nor is it conducive to improving the uniformity and consistency of the thickness of the pole piece; when the amount added is too little, the role of the surfactant is not obvious, and it is impossible to establish a good synergistic effect with other components, and the uniformity, uniformity and thinning edge thickness of the active coating thickness of the pole piece are not significantly improved.

[0044] In some embodiments, the weight ratio of the anionic surfactant to the nonionic surfactant is (5-10):(90-95).

[0045] In order to achieve a good synergistic effect with the positive electrode active material, conductive agent, binder and solvent, the present application controls the weight ratio of anionic surfactant to non-ionic surfactant to (5-10): (90-95), for example (6-9): (91-94); the obtained slurry coating the positive electrode plate has better leveling, dispersibility and uniformity, which is conducive to eliminating or alleviating the problem of thick edges of the active coating on the plate.

[0046] The hydrophobic group of the anionic surfactant selected in the present application is an alkyl group, the hydrophilic group is such as [R-CO-N-SO2-R']- of ketosulfonamide salt, the coordinated anion is such as [ROCe(NO3)5] - , amino acid salt R-CHNH2COO - , at least one of an enol group, an iodic acid group, an aldehyde group, a carboxyl group, a sulfuric acid group, a sulfonic acid group, a phosphoric acid group, an amino group, and a hydroxyl group.

[0047] In some embodiments, the anionic surfactant is selected from one or more of ammonium lauryl alcohol polyoxyethylene ether sulfate, disodium lauryl alcohol polyoxyethylene ether sulfosuccinate, sodium dodecylbenzene sulfonate, ammonium dodecyl polyacrylate, and sodium dioctyl sulfosuccinate.

[0048] The anionic surfactant selected in the present application has an appropriate number of polar groups, which can adsorb the solid particles suspended in the positive electrode slurry to bridge the particles or stabilize the particles through charge neutralization, so as to better enable the positive electrode slurry to have good dispersibility and rheology, reduce the surface tension of the positive electrode slurry, and further improve the thickness of the active coating edge of the positive electrode sheet during the coating process.

[0049] In some embodiments, the nonionic surfactant is selected from at least one of polyoxyethylene cetyl ether, polyoxypropylene cetyl ether, polyoxyethylene polyoxypropylene cetyl ether, nonylphenol polyoxyethylene ether, and ethylhexanol polyoxypropylene polyoxyethylene ether.

[0050] The nonionic surfactant selected in the present application contains both a hydrophobic alkyl chain and a hydrophilic oxygen-containing chain. The length of the alkyl chain and the oxygen-containing chain can reach the required HLB value and the corresponding decomposition, wetting and other properties; the above oxygen-containing chains mainly include hydroxyl groups and polyoxyethylene chains, such as polyol structures, alkyl alcohol amides and polyoxyethylene structures. The above-mentioned specific nonionic surfactant selected in the present application is in a nonionic state in aqueous solution, has higher stability, and has better solubility in both water and organic solvents. It can be used in water-based / oil-based slurries to promote the uniform dispersion of positive electrode active materials in different phases, so that the dispersed system has better rheological properties, thereby further improving the consistency of thinning the edge of the active coating of the electrode.

[0051] In some embodiments, the surfactant of the present application can specifically be selected from disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether. In particular, the slurry compounded in a weight ratio of 8:92 has better dispersibility and leveling properties, and significantly improves the thickness of the edge of the active coating of the electrode.

[0052] In some embodiments, the viscosity of the positive electrode slurry of the battery is 4000-5000 mPa·S; for example, the viscosity of the positive electrode slurry is any value of 4000, 4100, 4200, 4300, 4400, 4500, 4600, 4700, 4800, 4900, 5000 mPa·S or a range between any two values.

[0053] The present application regulates the viscosity of the positive electrode slurry to between 4000 and 5000 mPa·S. Appropriate viscosity is beneficial to the uniformity of slurry coating and the uniformity of electrode edge thickness, avoiding the thick edge phenomenon; too high or too low viscosity may lead to uneven coating, affecting the consistency and performance of the battery; appropriate viscosity is also beneficial to the fluidity of the slurry, and is beneficial to the battery's filling density, energy density, conductivity, stability and battery life.

[0054] In some embodiments, the solid content of the positive electrode slurry of the battery is 60% to 70%, for example 63%. The present application regulates the solid content of the positive electrode slurry to 60% to 70%. The appropriate solid content, i.e., the proportion of positive electrode active material, is appropriate, which is beneficial to improving the battery energy density, cycle stability, charge and discharge performance and safety.

[0055] In some embodiments, the weight ratio of the positive electrode active material, conductive agent, binder, solvent, and surfactant is (90-95): (1.5-5): (1-4): (0.01-2), for example (91-95): (1.5-5): (1-4): (0.05-1); further (91-95): (1.5-5): (1-4): (0.05-0.5); further (91-95): (1.5-5): (1-4): (0.05-0.2); the addition ratio of each component in the positive electrode slurry of the present application can also be adjusted according to actual conditions.

[0056] In some embodiments, the positive electrode active material is selected from nickel-cobalt-manganese ternary material, wherein the nickel content is ≥50%; the conductive agent is selected from one or more of conductive graphite, conductive carbon black and carbon nanotubes; further conductive carbon black; the binder is selected from polyvinylidene fluoride; and the solvent is selected from N-methylpyrrolidone. The positive electrode active material, conductive agent, binder, solvent, etc. of the present application can be selected from the prior art according to actual conditions.

[0057] According to the second aspect of the present application, a method for preparing the above-mentioned battery positive electrode slurry is provided, comprising the following steps: mixing raw materials of positive electrode active material, conductive agent, binder, solvent and surfactant according to the ratio of each raw material, stirring to obtain battery positive electrode slurry.

[0058] In some embodiments, the preparation method specifically comprises the following steps:

[0059] Step S1: mixing a binder and a solvent to form a glue solution; mixing a conductive agent and a solvent to form a conductive liquid;

[0060] Step S2: adding the positive electrode active material to the glue solution and the conductive liquid, adding a solvent for the first viscosity adjustment, adding a surfactant, stirring and dispersing, and performing a second viscosity adjustment until the viscosity of the slurry reaches a preset viscosity.

[0061] In some embodiments, the mass concentration of the glue solution is 8% to 20%; the mass concentration of the conductive liquid is 10% to 12%; and the preset viscosity is 4000 to 5000 mPa·S. The mixing method of the raw material components used in the present application is conducive to the uniformity of slurry dispersion.

[0062] According to the third aspect of the present application, a battery positive electrode plate is provided, comprising a positive electrode collector and a positive electrode active coating attached to the surface of the positive electrode collector; the slurry for preparing the positive electrode active coating is the above-mentioned battery positive electrode slurry.

[0063] The positive electrode slurry with good leveling properties, viscosity and surface energy of the present application is used to coat the positive electrode sheet, the thickness of the thinned area is small, the thickness of the active coating of the electrode sheet is consistent and uniform; there is no obvious thick edge phenomenon.

[0064] According to a fourth aspect of the present application, a battery is provided, comprising a positive electrode plate, which is the positive electrode plate of the above-mentioned battery.

[0065] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0066] Example 1

[0067] (1) Prepare the raw materials according to the following weight ratio: NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.95:0.05; wherein the surfactant is prepared by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92;

[0068] (2) The binder is uniformly dispersed in NMP solvent to obtain a glue solution with a mass concentration of 10%; the conductive agent is uniformly dispersed in the solvent to obtain a conductive liquid with a mass concentration of 12%; the surfactant is dispersed in the solvent to obtain a surfactant solution with a mass concentration of 1.2%; NCM523 active material, glue solution (10wt.%) and conductive solution (12wt.%) are added to a stirring tank in sequence, and after high-speed dispersion, solvent is added to adjust the viscosity to 8000mPa·S, and 0.05wt% of the surfactant solution by slurry mass is added and dispersed at a low speed for 30 minutes; the solvent is added again to ensure that the final slurry viscosity is 5000mPa·S and the slurry solid content is 63%; and then the surface of the aluminum foil current collector 1 is coated, rolled and cut in sequence to obtain a positive electrode sheet; the edge of the active coating has no obvious thick edge phenomenon; such as Figure 1 The coating thickness in the normal area is 3 and the coating thickness in the thinned area is 2.

[0069] Example 2

[0070] The difference between Example 2 and Example 1 is that the formula of each raw material in the slurry is different;

[0071] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.92:0.08; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0072] Example 3

[0073] The difference between Example 3 and Example 1 is that the formula of each raw material in the slurry is different;

[0074] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.9:0.1; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0075] Example 4

[0076] The difference between Example 4 and Example 1 is that the formula of each raw material in the slurry is different;

[0077] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.88:0.12; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0078] Example 5

[0079] The difference between Example 5 and Example 1 is that the formula of each raw material in the slurry is different;

[0080] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.99:0.01; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0081] Example 6

[0082] The difference between Example 6 and Example 1 is that the formula of each raw material in the slurry is different;

[0083] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.85:0.15; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0084] Example 7

[0085] The difference between Example 7 and Example 1 is that the formula of each raw material in the slurry is different;

[0086] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.8:0.2; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0087] Example 8

[0088] The difference between Example 8 and Example 1 is that the formula of each raw material in the slurry is different;

[0089] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.7:0.3; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0090] Example 9

[0091] The difference between Example 9 and Example 1 is that the formula of each raw material in the slurry is different;

[0092] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.5:0.5; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0093] Example 10

[0094] The difference between Example 10 and Example 1 is that the formula of each raw material in the slurry is different;

[0095] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.2:0.8; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0096] Embodiment 11

[0097] The difference between Example 11 and Example 1 is that the formula of each raw material in the slurry is different;

[0098] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.0:1.0; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0099] Example 12

[0100] The difference between Example 12 and Example 1 is that the formula of each raw material in the slurry is different;

[0101] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:2.5:1.5; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0102] Example 13

[0103] The difference between Example 13 and Example 1 is that the formula of each raw material in the slurry is different;

[0104] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:2.0:2.0; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 8:92.

[0105] Embodiment 14

[0106] The difference between Example 14 and Example 1 is that the formula of each raw material in the slurry is different;

[0107] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.9:0.1; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 5:95.

[0108] Embodiment 15

[0109] The difference between Example 15 and Example 1 is that the formula of each raw material in the slurry is different;

[0110] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.9:0.1; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 10:90.

[0111] Example 16

[0112] The difference between Example 16 and Example 1 is that the formula of each raw material in the slurry is different;

[0113] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.9:0.1; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 15:85.

[0114] Embodiment 17

[0115] The difference between Example 17 and Example 1 is that the formula of each raw material in the slurry is different;

[0116] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.9:0.1; wherein the surfactant is formed by compounding sodium dodecylbenzene sulfonate and polyoxyethylene cetyl ether in a weight ratio of 8:92.

[0117] Embodiment 18

[0118] The difference between Example 18 and Example 1 is that the formula of each raw material in the slurry is different;

[0119] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.9:0.1; wherein the surfactant is formed by compounding dioctyl sodium sulfosuccinate and polyoxyethylene polyoxypropylene hexadecyl ether in a weight ratio of 8:92.

[0120] Embodiment 19

[0121] The difference between Example 19 and Example 1 is that the formula of each raw material in the slurry is different;

[0122] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.9:0.1; wherein the surfactant is formed by compounding dodecyl ammonium polyacrylate and ethylhexanol polyoxypropylene polyoxyethylene ether in a weight ratio of 8:92.

[0123] Embodiment 20

[0124] The difference between Example 20 and Example 1 is that the formula of each raw material in the slurry is different;

[0125] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.9:0.1; wherein the surfactant is formed by compounding disodium lauryl polyoxyethylene ether sulfosuccinate, dioctyl sodium sulfosuccinate, nonylphenol polyoxyethylene ether and polyoxyethylene cetyl ether in a weight ratio of 4:4:46:46.

[0126] Comparative Example 1

[0127] The difference between Comparative Example 1 and Example 1 is that no surfactant is added to the slurry.

[0128] NCM523 active material: SP conductive agent: PVDF binder is 93:3:4.0.

[0129] Comparative Example 2

[0130] The difference between Comparative Example 2 and Example 1 is that the surfactant added to the slurry is an anionic surfactant; the ratio of NCM523 active material: SP conductive agent: PVDF binder: anionic surfactant is 93:3:3.9:0.1; wherein the anionic surfactant is disodium lauryl polyoxyethylene ether sulfosuccinate.

[0131] Comparative Example 3

[0132] The difference between Comparative Example 3 and Example 1 is that the surfactant added to the slurry is a non-ionic surfactant; the ratio of NCM523 active material: SP conductive agent: PVDF binder: non-ionic surfactant is 93:3:3.9:0.1; wherein the non-ionic surfactant is nonylphenol polyoxyethylene ether.

[0133] Comparative Example 4

[0134] The difference between Comparative Example 4 and Example 1 is that the ratio of surfactant added to the slurry is different; NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:1.8:2.2.

[0135] Comparative Example 5

[0136] The difference between Comparative Example 5 and Example 1 is that the formulas of the raw materials in the slurry are different;

[0137] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.9:0.1; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 3:97.

[0138] Comparative Example 6

[0139] The difference between Comparative Example 6 and Example 1 is that the formulas of the raw materials in the slurry are different;

[0140] The ratio of NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.9:0.1; wherein the surfactant is formed by compounding disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether in a weight ratio of 20:80.

[0141] Comparative Example 7

[0142] The difference between Comparative Example 7 and Example 1 is that different surfactants are added to the slurry; NCM523 active material: SP conductive agent: PVDF binder: surfactant is 93:3:3.9:0.1; the surfactant is formed by compounding ammonium dodecyl sulfate and polyoxyethylene dodecyl ether in a weight ratio of 5:5.

[0143] The thickness of the thinned area of ​​the positive electrode sheets of Examples 1 to 20 and Comparative Examples 1 to 7 was measured.

[0144] Table 1

[0145]

[0146]

[0147]

[0148] Note: The slurry in comparative example 5 is too thin and the coating is abnormal;

[0149] The test results of the active coating thickness of the positive electrode plates in Table 1 show that the coating thickness of the normal area of ​​the positive electrode plates prepared by coating in Examples 1 to 20 is 103.0 μm, and the coating thickness of the thinned area is concentrated between 93.0 and 96.2 μm; among them, when the amount of surfactant added is 0.1%, the thickness of the thinned area of ​​the positive electrode plates is relatively smaller, and the thick edge improvement effect is better.

[0150] In Comparative Example 1, no surfactant is added to the positive electrode slurry; the coating thickness of the thinned area is 110.2 μm, which is 14 to 17.2 μm thicker than the coating thickness of the thinned area of ​​the pole piece of the embodiment of the present application. This shows that the present application can significantly reduce the coating thickness of the thinned area by adding a specific proportion of a composite surfactant to the positive electrode slurry, so that the coating thickness of the positive electrode piece has a uniform effect, thereby improving the consistency and stability of the battery performance.

[0151] In Comparative Example 2, only anionic surfactant was added to the positive electrode slurry; the coating thickness of the thinned area was 102.1 μm, which was about 6 to 9 μm thicker than the coating thickness of the thinned area of ​​the electrode sheet in the embodiment of the present application. This shows that only adding anionic surfactant to the positive electrode slurry has no obvious effect on improving the thickness of the positive electrode sheet coating edge.

[0152] In Comparative Example 3, only nonionic surfactant was added to the positive electrode slurry; the coating thickness of the skived area was 100.5 μm, which was about 4 to 7 μm thicker than the coating thickness of the skived area of ​​the pole piece in the embodiment of the present application. This shows that although the surfactant is mainly nonionic surfactant, supplemented by anionic surfactant, the effect of adding nonionic surfactant only to the positive electrode slurry on improving the thickness of the negative electrode coating edge is still limited, and the two surfactants need to be compounded in a specific ratio to further improve the thickness improvement effect.

[0153] In Comparative Example 4, the surfactant ratio added to the positive electrode slurry is 2.2%; the slurry fluidity is too strong during coating, resulting in large fluctuations in the surface density of the electrode sheet, and it cannot be effectively coated. This shows that even if the two specific addition ratios of surfactants in this application are used, if the addition amount is too large, it is not conducive to improving the thickness of the positive electrode sheet coating edge.

[0154] In Comparative Example 5, the ratio of anionic surfactant to nonionic surfactant added to the positive electrode slurry is 3:97; the coating thickness of the thinned area is 98.4 μm, which is about 2 to 5 μm thicker than the coating thickness of the thinned area of ​​the electrode sheet in the embodiment of the present application. This shows that even if the composite surfactant with a specific addition ratio of the present application is used, the ratio of anionic surfactant to nonionic surfactant is not appropriate. For example, when the amount of nonionic surfactant is too large, the problem of thick edge of the positive electrode sheet coating cannot be effectively improved.

[0155] In Comparative Example 6, the compounding ratio of anionic surfactant and nonionic surfactant added to the positive electrode slurry is 20:80; the coating thickness of the thinned area is 98.9 μm, which is about 2 to 6 μm thicker than the coating thickness of the thinned area of ​​the pole piece in the embodiment of the present application. This shows that even if the compounding surfactant with a specific addition ratio of the present application is used, the compounding ratio of anionic surfactant and nonionic surfactant is not appropriate. For example, if the amount of nonionic surfactant is too small, it still cannot effectively improve the problem of thick edge of the positive electrode coating.

[0156] In Comparative Example 7, the anionic surfactant and nonionic surfactant added to the positive electrode slurry are of different types, and the compounding ratio is 5:5; the coating thickness of the thinned area is 100.2 μm, which is about 4 to 7 μm thicker than the coating thickness of the thinned area of ​​the electrode sheet in the embodiment of the present application. This indicates that when other different types of surfactants are selected and an inappropriate compounding ratio is used, the effect of improving the thickness of the positive electrode sheet coating edge is poor.

[0157] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0158] The above description is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A battery positive electrode slurry, characterized in that: The components of the battery positive electrode slurry include positive electrode active material, conductive agent, binder, solvent and surfactant; The added amount of the surfactant is 0.01-2wt% of the total amount of the battery positive electrode slurry; the surfactant is compounded by anionic surfactant and nonionic surfactant in a weight ratio of (5-15): (85-95).

2. The battery positive electrode slurry according to claim 1, characterized in that: The added amount of the surfactant is 0.05-1.5 wt % of the total amount of the electrode slurry; preferably 0.05-1 wt %; more preferably 0.08-0.5 wt %; and even more preferably 0.08-0.2 wt %.

3. The positive electrode slurry for battery according to claim 1 or 2, characterized in that: The weight ratio of the anionic surfactant to the nonionic surfactant is (5-10):(90-95).

4. The positive electrode slurry for a battery according to any one of claims 1 to 3, characterized in that: The anionic surfactant is selected from at least one of ammonium dodecyl alcohol polyoxyethylene ether sulfate, disodium dodecyl alcohol polyoxyethylene ether sulfosuccinate, sodium dodecylbenzene sulfonate, ammonium dodecyl polyacrylate and dioctyl sodium sulfosuccinate.

5. The positive electrode slurry for a battery according to any one of claims 1 to 4, characterized in that: The nonionic surfactant is selected from at least one of polyoxyethylene cetyl ether, polyoxypropylene cetyl ether, polyoxyethylene polyoxypropylene cetyl ether, nonylphenol polyoxyethylene ether and ethylhexanol polyoxypropylene polyoxyethylene ether.

6. The positive electrode slurry for a battery according to any one of claims 1 to 5, characterized in that: The surfactant is composed of disodium lauryl alcohol polyoxyethylene ether sulfosuccinate and nonylphenol polyoxyethylene ether; And / or, the viscosity of the battery positive electrode slurry is 4000-5000 mPa·S; And / or, the solid content of the battery positive electrode slurry is 60% to 70%.

7. The positive electrode slurry for a battery according to any one of claims 1 to 6, characterized in that: The weight ratio of the positive electrode active material, the conductive agent, the binder, and the surfactant is (90-95): (1.5-5): (1-4): (0.01-2); Preferably, the positive electrode active material is selected from nickel-cobalt-manganese ternary material; further preferably, the nickel content in the nickel-cobalt-manganese ternary material is ≥50wt%; Preferably, the conductive agent is selected from at least one of conductive graphite, conductive carbon black and carbon nanotubes; preferably conductive carbon black; Preferably, the binder is selected from polyvinylidene fluoride; Preferably, the solvent is selected from N-methylpyrrolidone.

8. The method for preparing a positive electrode slurry for a battery according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: mixing raw materials of positive electrode active material, conductive agent, binder, solvent and surfactant according to respective raw material ratios, stirring to obtain the positive electrode slurry of the battery; Preferably, the preparation method specifically comprises the following steps: Step S1: mixing the binder and the solvent to form a glue solution; mixing the conductive agent and the solvent to form a conductive liquid; mixing the surfactant and the solvent to form a surfactant solution; Step S2: adding the positive electrode active material to the glue solution and the conductive liquid, adding the solvent to adjust the viscosity for the first time, then adding the surfactant solution, and adding the solvent to adjust the viscosity for the second time until the viscosity of the slurry reaches a preset viscosity; Preferably, the mass concentration of the glue solution is 8% to 20%; Preferably, the mass concentration of the conductive liquid is 10% to 12%; Preferably, the mass concentration of the surfactant solution is 0.8% to 1.5%; Preferably, the preset viscosity is 4000-5000 mPa·S.

9. A battery positive electrode plate, comprising a positive electrode current collector and a positive electrode active coating attached to the surface of the positive electrode current collector; characterized in that: The slurry for preparing the positive electrode active coating is the battery positive electrode slurry according to any one of claims 1 to 7.

10. A battery comprising a positive electrode plate, characterized in that: The positive electrode plate is the positive electrode plate of the battery according to claim 9.

Citation Information

Patent Citations

  • Composite dispersing agent, positive pole material composition and positive pole thereof, and lithium-ion secondary battery

    CN101757875A

  • Preparation method of nanometer conductive carbon black suspension, battery anode and battery

    CN101763911A

  • Positive electrode paste, preparation method thereof, positive electrode and lithium ion battery

    CN109755533A

  • Dispersing agent for lithium iron phosphate positive electrode slurry, lithium iron phosphate positive electrode slurry, preparation method of lithium iron phosphate positive electrode slurry and lithium ion battery

    CN115498190A

  • Lithium ion battery water-based positive electrode slurry and preparation method thereof

    CN116504980A